Extractive desulfurization of fuels using modified ionic liquids with magnetic graphene oxide from refused dry cell batteries. (15th November 2022) - Laraib, Sofia; Zulfiqar, Sana; Tabassum, Noshaba; Andleeb, Sohaila; Nasreen, Saima
Highlights: This research is designed to tackle the remediation of sulfur content from model fuels and from commercial fuels. This research is aiming to add a novel magnetic graphene oxide ionic liquids that have unique anion and cation combination (not reported previously). The employed method for the desulfurization using HPLC is quite fast. convenient and most accurate to amplify the results. The study is environmental friendly and it utilizes the refused dry cells as a source of graphite. Abstract: Humanity is facing the biggest hazard in the form of systematic pollution of environment. Significant dwindling resources is a sign of rapid population explosion. Due to increasing human population, the burden on environment is also increasing exponentially leaving serious concerns about greenhouse gases induced climate change, energy security as well as the air, land and water quality deterioration. These concerns are driving the development of alternate energy solutions and to modify fuels with high sulfur and nitrogen content to mitigate cleaner fuel crises in the developing countries like Pakistan. To this end, Graphene oxide-GO (synthesized from refused dry cell batteries) and Magnetic Graphene oxide-MGO based ionic liquids (ILs) were synthesized and fabricated with cellulose acetate (CA) for their potential applications in desulfurization of fuel. Synthesized ILs were characterized by different techniques such as Attenuated Total Reflectance (ATR-FTIR), Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD) and Cyclic Voltammetry (CV). Close batch experiments were designed to evaluate the desulfurization and adsorption capabilities of prepared liquids under varying parameters. Moreover, HPLC and UV–Visible spectrophotometer were used to determine the reduction of thiophene peaks and extent of desulfurization (%R > 98.9 % and 91 % for Model fuel and Crude fuel, respectively). The proposed study offers an economical and eco-friendly material that have open up a wider application window and owing to the surface modifications these hybrid materials with multi-functional groups are expected to reduce the pollution load from multi-compartment simultaneously.